Performance changes in rowers after training aiming for improvement of the individual physiological profile estimated by five performance trials in four days - Jensen, K.; Lippits, R.; de Boorder, D. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Rowers perform over 2000m (5.3-7.5 min), but although they follow the same training program and look similar from a physical performance point of view, genetics and training history may have a great influence upon their individual physical profile and adaptation to training. It might be hypothesed that individual terms should be taken, i.e. that rowers with low max power should be motivated to do special power sessions, and equivalent, less powerful rowers, a program based on steady aerobic work. Hence, they should develop against a more balanced profile. Therefore, the aim of the current study was 1) to evaluate performance changes during a winter season and 2) focus on individual based training for development of performance aiming a more balanced profile in a group of young talented rowers. Methods: Twenty Dutch university rowers, 14 males and 6 females: age 21.2±2.0 years, systematic rowing experience 2.2±1.2 years, from Regional Talent Center, Rowing (Brabant) were tested at the beginning of the winter season and after 16 weeks. Average power was measured during five all out tests on a Concept II rowing ergometer on four consecutive days: 1: 6km (W6k) and best of 3 times 100m (W100m); 2: 2km (W2k); 3: 1 min (W1min); 4: 60 min (W60min). Free stroke rate and drag factor setting were allowed. W2k was used as reference, resulting in a relative intensity in relation to work time: "the power endurance curve" (Jensen, 2007). Training consisted of 30 min in a rowing ergometer, 6 days per week, alternating between intensities defined by each rower`s individual performance profile (70-170% W2k). Each session was followed by 45 min in the boat with low intensity (~60-75% W2k). Results: The performance increased by 3.5, 5.9, 8.5, 9.5 and 10.1% in W100m; W1min; W2k; W6k; and W6min, respectively (p<0.05) bringing the group from 22% to 15% below the selection criteria for the national team. The different relation between high intensity performance and endurance was indicated by W100m relative to W60min: 2.39±0.21 vs 2.55±0.29 (P<0.05) while other relations between performance tests remained unchanged (P>0.05). The relative changes between short and longer tests indicate that the profile is balanced more in direction of the golden standard (Jensen, 2007) Discussion: This study demonstrated that aerobic endurance increased by 9-10% during winter season in this group of relative unexperienced (<23years) rowers after 16 weeks and by only 6-8 hours of weekly training. More importantly the rowers changed their profile from more strength and power dependent to be more aerobic trained.